A practical guide to cluster randomised trials in health services research - Eldridge, Sandra; Kerry, Sally M. (Chichester, West Sussex : John Wiley & Sons, 2012)
"There is relatively little literature on cluster randomized trials, with only two previous books on the subject, both now quite old, and neither were focused on the practical aspects of the trials. This book provides that much needed practical guide to the design, execution and analysis of cluster randomized trials in health services research. It also provides an overview of the topic's numerous recent developments since the 2000 publication of the last book in this area. The opening chapter defines and introduces cluster randomized trials, before going on to present an overview of the subject's history and recent developments. The following chapters focus on all the major issues presented in the order in which investigators think about issues when they are designing a trial. The chapters focus on: trial quality, reporting, how to design an intervention, how to ensure the validity of results, how to choose both the design and the analysis of the trial, sample size calculations, choosing an intra-cluster correlation coefficient, the uses of piloting, how to conduct a cost-effectiveness analysis, and how these trials should be synthesized. The book also contains numerous tables, graphs and diagrams and a substantial number of recent trials"--Provided by publisher.
"This book aims to provide that much needed practical guide to the design, execution and analysis of cluster randomized trials in health services research"--Provided by publisher.
Front Matter -- Introduction -- Recruitment and Ethics -- Designing Interventions -- Pilot and Feasibility Studies -- Design -- Analysis -- Sample Size Calculations -- The Intra-Cluster Correlation Coefficient -- Other Topics / Richard Grieve -- Trial Reporting -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Medical care -- Research; Evidence-based medicine; Health Services Research; Randomized Controlled Trials as Topic; Cluster Analysis; Evidence-based medicine; Medical care -- Research; Electronic books; Electronic books